Religions and education in antiquity : studies in honour of Michel Desjardins - Damm, Alex, (Numen Book Series, 2018)
Religions and Education in Antiquity gathers ten essays on teaching and learning in the contexts of ancient Western religions, including Judaism, early Christianity and Gnostic Christian traditions. Beginning with an overview of religious education in the ancient Near Eastern and Mediterranean worlds, editor Alex Damm and the contributors together demonstrate the mutual influence of religion and education on each other; the relevance of educational traditions in addressing (for instance) historical or exegetical issues; and the thoroughgoing importance of education to religious life across time and space in antiquity. Highly useful to scholars of religion, theology, classics and education, this volume affords a state of the art study on pedagogy and learning in ancient religious contexts.